The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nu12051482
|View full text |Cite
|
Sign up to set email alerts
|

Tart Cherry Increases Lifespan in Caenorhabditis elegans by Altering Metabolic Signaling Pathways

Abstract: Aging and healthspan are determined by both environmental and genetic factors. The insulin/insulin-like growth factor-1(IGF-1) pathway is a key mediator of aging in Caenorhabditis elegans and mammals. Specifically, DAF-2 signaling, an ortholog of human IGF, controls DAF-16/FOXO transcription factor, a master regulator of metabolism and longevity. Moreover, mitochondrial dysfunction and oxidative stress are both linked to aging. We propose that daily supplementation of tart cherry extract (TCE), rich in anthocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…Many studies have focused on the anti-oxidant capacity of different plant extracts rich with anthocyanins. The vast majority of plant extracts rich in anthocyanins, such as extracts of purple wheat (Chen et al, 2013 ), acai berry (Peixoto et al, 2016 ), mulberry (Yan et al, 2017 ), purple pitanga fruit (Tambara et al, 2018 ), tart cherry (Jayarathne et al, 2020 ), and bilberry (Gonzalez-Paramas et al, 2020 ), which can play their beneficial role by increasing nuclear translocation of DAF-16 and promoting the expression of anti-oxidant genes, such as sod-3 , and the heat shock gene, hsp-16.2 , in its downstream. Heat shock proteins (HSPs) are molecular chaperones and play important roles in the protection of molecular damage under environmental stress and have the ability to maintain proteostasis and prolong the longevity of organisms (Swindell, 2009 ).…”
Section: Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have focused on the anti-oxidant capacity of different plant extracts rich with anthocyanins. The vast majority of plant extracts rich in anthocyanins, such as extracts of purple wheat (Chen et al, 2013 ), acai berry (Peixoto et al, 2016 ), mulberry (Yan et al, 2017 ), purple pitanga fruit (Tambara et al, 2018 ), tart cherry (Jayarathne et al, 2020 ), and bilberry (Gonzalez-Paramas et al, 2020 ), which can play their beneficial role by increasing nuclear translocation of DAF-16 and promoting the expression of anti-oxidant genes, such as sod-3 , and the heat shock gene, hsp-16.2 , in its downstream. Heat shock proteins (HSPs) are molecular chaperones and play important roles in the protection of molecular damage under environmental stress and have the ability to maintain proteostasis and prolong the longevity of organisms (Swindell, 2009 ).…”
Section: Anthocyaninsmentioning
confidence: 99%
“…DAF-16 is a key protein for the anti-aging effects. Mechanistically, recent studies have found that anthocyanins could regulate the AAK-2/AMPK signaling pathway to perform its biological function (Jayarathne et al, 2020 ). aak-2 is the encoding gene of AMPK in nematodes.…”
Section: Anthocyaninsmentioning
confidence: 99%
“…Changes during aging are often linked to mitochondrial dysfunction. For the first time, we demonstrated that worms fed TC extracts exhibited increased mitochondrial spare respiration, and expression of uncoupling protein 4 and antioxidant markers such as superoxide dismutase (SOD)-3 [59]. Additional research is warranted both in mouse models and clinical studies to better understand the detailed molecular mechanisms of TC in aging and determine the most effective dose for human consumption.…”
Section: Role Of Tart Cherry (Tc) In the Prevention Of Obesity-related Inflammation And Life Span Extensionmentioning
confidence: 99%
“…Dietary antioxidants have potential roles in lowering oxidative stress associated with aging and chronic conditions [58]. We have recently reported that TC extract rich in anthocyanins with antioxidant activity increased lifespan in C. elegans mainly via insulin/insulin-like growth factor-1 signaling (IIS) by regulating DAF-2 and DAF-16 expression, major components of the IIS pathway [59]. Changes during aging are often linked to mitochondrial dysfunction.…”
Section: Role Of Tart Cherry (Tc) In the Prevention Of Obesity-related Inflammation And Life Span Extensionmentioning
confidence: 99%
“…E. coli DA837 and Bacillus simplex are intermediate food sources [39]. Additionally, several investigations reported that food sources that contain phytochemicals such as blueberry polyphenols [40], epigallocatechin gallate from tea [41], plant adaptogens [42], and tart cherry [43], among others, increase the life span of C. elegans.…”
Section: Dietmentioning
confidence: 99%